Defibrillation success during different phases of the mechanical chest compression cycle. (June 2016) - Steinberg, Mikkel T.; Olsen, Jan-Aage; Brunborg, Cathrine; Persse, David; Sterz, Fritz; Lozano Jr, Michael; Westfall, Mark; Travis, David T.; Lerner, E. Brooke; Wik, Lars
Abstract: Introduction: Animal studies indicate higher termination of VF/VT (TOF) rates after shocks delivered during the decompression phase of the compression cycle for manual and mechanical CPR. We investigated TOF for shocks delivered in different compression cycle phases during load distributing band (LDB) mechanical CPR in the CIRC trial. Methods: Shocks were retrospectively categorized as delivered during the compression, decompression, or relaxation phase of LDB compressions using transthoracic impedance data. Shocks delivered when the LDB device was paused, were used as controls. The first shock and the first up-to-three shocks (first shocks plus shocks two and three if given) from patients with initial VF/VT and LDB CPR prior to shock were grouped according to compression cycle phase. TOF rates for these groups versus the control group were analyzed using logistic regression for first shocks and the general estimating equations (GEE) model for the up-to-three shocks. Adjustments were made for bystander CPR, witnessed arrest, defibrillator shock energy and transthoracic impedance. Results: Among 244 first shocks and 685 up-to-three shocks TOF success rates were lower ( p  < 0.05 and p  < 0.02) for shocks given during the compression phase (72% and 71% respectively) than for control shocks given during compression pauses (86% and 82% respectively). Decompression and relaxation phase shocks had TOF rates not different from the controls. Conclusion: Shocks delivered in the compression phase of LDB chest compressions had lower TOF rates than shocks delivered while pausing the LDB device. More research is needed to see how defibrillation during chest compressions affect ROSC and survival.